Crotalaria nallamalayana (Fabaceae: Crotalarieae): a new species from Telangana, India - Rasingam, Ladan; Swamy, Jetti; Sankara Rao, Mudadla (Phytotaxa, 2018)
A new species of Crotalaria is described from the Amrabad Tiger Reserve in the Nallamala forest, Telangana, India. It is allied to Crotalaria orixensis Rottl. ex Willd. and Crotalaria senegalensis (Pers.) DC., but differs from both species in leaf, stipule, bract and floral characters.